KEPEMIMPINAN KOPRS SUKARELA PALANG MERAH INDONESIA; UPAYA MENINGKATKAN SKILL ANGGOTA - Megariani; MY, Mahmud; Chaniago, Fransisko; Fitriani, Suci; Summiyani; Afifah, Yuliana (re-JIEM (Research Journal of Islamic Education Management), 2023)
This study aims to determine the leadership strategy used in improving members' skills and to find out the stages and inhibiting factors of activities related to improving the skills of members in the Organizational Special Activity Unit of the Indonesian Red Cross Voluntary Corps at UIN Sulthan Thaha Saifuddin Jambi Higher Education. This research is field research, namely by collecting data in the field. This study uses interview techniques, observation, and interviews. The research results show that the Indonesian Red Cross Volunteer Corps Leadership Strategy to Improving Member Skills, namely providing teaching material and practice in accordance with the skills in their respective fields. The stages of activities involved in improving members' skills are basic room education and training, field education and training, permanent member education and training, joint training with Basarnas, basic organizational leadership training, and weekly member training. As for the supporting factors, the leader always instills a positive spirit in the members in the process of improving their skills of the members. While the inhibiting factors are first, the implementation of the role of administrators is not in accordance with basic organizational leadership training, second, some members have not been able to manage time between academics and organizations so members tend to do excessive activities, and third, regarding campus funding for organizational activities sometimes not according to what the manager said.